1993
DOI: 10.1152/ajplung.1993.265.6.l613
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide stimulates sodium-potassium pump activity in cultured pulmonary arterial endothelial cells

Abstract: Oxidant injury to pulmonary vascular endothelium is an important factor in the pathogenesis of acute lung injury. Oxidant injury to other cell types has been reported to alter the function of Na-K-adenosinetriphophatase (ATPase) an enzyme important in maintenance of cellular ionic homeostasis and in transport of ions across biological membranes. We investigated the effect of H2O2 (0.001-10 mM) or xanthine (X) (15.2 micrograms/ml) plus xanthine oxidase (XO) (0.0153 U/ml) on the Na-K pump activity of cultured bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Furthermore, in both normal subjects and patients with essential hypertension local insulin infusion in physiological amounts potentiates acetylcholine-induced vasodilatation [60]. Both cell types carry insulin receptors as well as Na þ -K þ -ATPase activity in their plasma membrane [61,62], and can synthesise and release NO. Both cell types carry insulin receptors as well as Na þ -K þ -ATPase activity in their plasma membrane [61,62], and can synthesise and release NO.…”
Section: Vasodilatation Anti(platelet)-aggregationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in both normal subjects and patients with essential hypertension local insulin infusion in physiological amounts potentiates acetylcholine-induced vasodilatation [60]. Both cell types carry insulin receptors as well as Na þ -K þ -ATPase activity in their plasma membrane [61,62], and can synthesise and release NO. Both cell types carry insulin receptors as well as Na þ -K þ -ATPase activity in their plasma membrane [61,62], and can synthesise and release NO.…”
Section: Vasodilatation Anti(platelet)-aggregationmentioning
confidence: 99%
“…The exact site of this action of insulin, whether the endothelial or the smooth muscle cell, is not known with certainty. Both cell types carry insulin receptors as well as Na þ -K þ -ATPase activity in their plasma membrane [61,62], and can synthesise and release NO. In cultured smooth muscle [63] insulin attenuates agonistinduced increases in intracellular calcium concentrations ([Ca 2þ ] i ) thereby causing relaxation.…”
Section: Vasodilatation Anti(platelet)-aggregationmentioning
confidence: 99%
“…Ex vivo studies treating preconstricted preparations of human coronary, pulmonary and radial arteries with insulin have revealed dose‐dependent endothelium‐dependent relaxation; 54 however, it is not known whether the effect of insulin in these models is to stimulate production of a vasodilator substance, such as NO, from the endothelium or to attenuate the efficacy of the experimental vasoconstrictor. It has also been proposed that the mechanism by which insulin stimulates endothelial NO production may be via its action on endothelial Na + /K + ‐ATPase; 55 , 56 as there are no voltage‐gated Ca 2+ channels in endothelial cells, hyperpolarization leads to an increase in intracellular [Ca 2+ ], 57 which may activate the Ca 2+ ‐dependent enzyme endothelial NOS.…”
Section: Mechanisms Of the Vasodilator Action Of Insulinmentioning
confidence: 99%
“…7 We found that short-term exposure (30 min) to reagent H202 and xanthine/xanthine oxidase stimulate pulmonary arterial endothelial Na/K pump activity (Fig l). 8 Hydrogen peroxide decreased intracellular ATP con¬ tent; thus, changes in ATP content did not account for increased pump activity.8 Scatchard analysis indicated that the number of endothelial cell 3H-ouabain binding sites was decreased by H202.8 Cell membrane expression of ax Na/K pump subunit, as assessed by Western blots, was not altered by H202.7 Thus, increased numbers of membrane pump sites did not account for oxidant-induced enhance¬ ment of Na/K pump activity.…”
Section: Resultsmentioning
confidence: 99%